Wnt/beta-catenin pathway in the prefrontal cortex is required for cocaine-induced neuroadaptations - Cuesta, Santiago (2017)
Fil: Fil: Cuesta, Santiago. Consejo Nacional de Investigaciones Científicas y Técnicas (CONICET); Argentina.